The Effect of Culturally-Based Conversations on Developing Speaking Skill among Peruvian Upper-Intermediate EFL Learners - Menacho-Vargas, Isabel; Garcia, Ulises Córdova; Rojas, Milagritos Leonor Rodríguez; Wong-Fajardo, Emma Margarita; Saavedra-López, Miguel A (International journal of society, culture & language, 2021)
This empirical research intended to seek the effects of culturally-based conversations on developing speaking skill among Peruvian upper-intermediate EFL students. To reach this purpose, the OQPT was administered to 158 EFL students to gauge their general proficiency in the English language. After that, the researchers chose 100 upper-intermediate students and made them two groups; culture group (n=50) and conventional group (n=50). Then, the researchers gave a speaking pre-test to the mentioned groups. After pre-testing, the culture group received the instruction through culturally-based conversations, i.e., conversations that were related to American and English cultures. The conventional group was instructed traditionally, i.e., they did not receive any specific culturally-based conversations. This procedure continued till the last session. Finally, the researchers gave a speaking post-test to the subjects of both groups. The analysis of the data revealed that the culture group outflanked the conventional group after the treatment. Eventually, the benefits of the cultural materials for teachers and students were described.